Five Year Plan Assam District and Subdivisional Series Nowgong - Government of Assam (Government of Assam, 1955)
The Five-Year Plan (1951-56) for Nowgong District in Assam provides a structured framework for regional development, emphasizing improvements across agriculture, public health, education, infrastructure, and community welfare. Governance is facilitated through Subdivisional Development Committees led by the Deputy Commissioner, involving local officials and representatives to implement state-wide initiatives and plan future schemes. The district was allocated ₹155.16 lakhs, with ₹52.42 lakhs expended during the first three years across categories such as the General Plan, Expansion Projects, Community Projects, Local Development Works, and schemes under Article 275 of the Constitution. Key interventions included minor irrigation projects and seed distribution to boost agricultural productivity, vaccination campaigns and healthcare improvements, establishment and support of schools, road construction to enhance rural connectivity, and rural water supply schemes. Community development efforts focused on self-help groups and cooperative societies to strengthen social engagement and local empowerment. Achievements by 1952-53 include increased agricultural output, new roads, and improved access to health and education services, with projections for 1953-54 highlighting continued growth. The plan underscores transparency, fiscal accountability, and participatory governance, setting a foundation for future development initiatives and the effective formulation of a Second Five-Year Plan aimed at sustainable socio-economic improvement across Nowgong District.
Department of Planning and Development Government of Assam
Department of Planning and Development Government of Assam
Keywords: Nowgong District; Assam Five-Year Plan; Subdivisional Development Committees; Agriculture; Irrigation; Education; Public Health; Infrastructure; Road Construction; Water Supply; Community Projects; Article 275 Schemes